2019
DOI: 10.3390/ijms21010286
|View full text |Cite
|
Sign up to set email alerts
|

The Soybean GmNAC019 Transcription Factor Mediates Drought Tolerance in Arabidopsis in an Abscisic Acid-Dependent Manner

Abstract: Being master regulators of gene expression, transcription factors (TFs) play important roles in determining plant growth, development and reproduction. To date, many TFs have been shown to positively mediate plant responses to environmental stresses. In the current study, the biological functions of a stress-responsive NAC [NAM (No Apical Meristem), ATAF1/2 (Arabidopsis Transcription Activation Factor1/2), CUC2 (Cup-shaped Cotyledon2)]-TF encoding gene isolated from soybean (GmNAC019) in relation to plant drou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…In addition, our findings indicated that the ectopic expression of GmRR34 resulted in retarded growth in the transgenic plants under normal growth conditions ( Figure 1B-D). Previous studies also reported on similar phenotypic alteration in relation to improved drought tolerance/resistance when using constitutive 35S promoter to drive the expression of transgenes in various transgenic species, including Arabidopsis [40][41][42], tobacco [43,44], and tomato [45,46].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, our findings indicated that the ectopic expression of GmRR34 resulted in retarded growth in the transgenic plants under normal growth conditions ( Figure 1B-D). Previous studies also reported on similar phenotypic alteration in relation to improved drought tolerance/resistance when using constitutive 35S promoter to drive the expression of transgenes in various transgenic species, including Arabidopsis [40][41][42], tobacco [43,44], and tomato [45,46].…”
Section: Discussionmentioning
confidence: 63%
“…During drought events, in addition to the electron transport chain activities in the chloroplast, photorespiration which is caused by stomatal closure is another source for extensive ROS production, especially H 2 O 2 [66,67]. Therefore, endogenous H 2 O 2 levels and detoxification activities by enzymes are commonly measured as important parameters in drought tolerance studies [40,42]. As 14-day-drought duration used in the survival test would be too severe and thus cause difficulties in analyzing biochemical data due to protein degradation and plant death, we determined to use a shorter stress duration (i.e., 10 days) for these assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genes had similar genomic organization and high sequence similarity, especially in the NAC domains, but exhibited different expression patterns during seed development [ 108 ]. Subsequently, more NAC proteins were identified in soybean [ 109 ], most of which are involved in development and abiotic stress, such as GmNAC30 [ 110 ], GmNAC81 [ 110 , 111 ], GmNAC109 [ 112 ] and GmNAC8 [ 113 ], while up to now only GmNAC42 is reported to be involved in plant disease resistance [ 114 , 115 , 116 ]. Soybean GmNAC42-1 is a homolog of the Arabidopsis ANAC042-1, which is an indole alkaloid plant antitoxin regulator.…”
Section: Nac Tfs Have Positive or Negative Roles In Crop Disease Rmentioning
confidence: 99%
“…The promoter of ABA-responsive genes possesses ABA-responsive elements (ABRE), which can bind to ABRE-binding proteins (ABREBPs) and activate transcription under ABA stimulation [ 20 ]. In addition, several transcription factors (TFs) of the bZIP, MYB, MYC, NAC, ERF, WRKY, and DREB protein families regulate gene expression in an ABA-dependent manner [ 21 , 22 , 23 , 24 , 25 ]. Typically, ABA-induced genes primarily encode the proteins associated with dehydrins and the enzymes that detoxify reactive oxygen species, enzymes of compatible solute metabolism, a variety of transporters, protein kinases and phosphatases, and the enzymes involved in phospholipid signaling.…”
Section: Introductionmentioning
confidence: 99%